Imaging biomarkers of NAFLD, NASH, and fibrosis - Ajmera, Veeral; Loomba, Rohit (Molecular metabolism (Germany), 2021)
Non-alcoholic fatty liver disease (NAFLD) is a clinicopathologic entity that requires a liver biopsy assessment to diagnose the progressive form of NAFLD called non-alcoholic steatohepatitis (NASH). Liver biopsy is invasive, subject to sampling and interobserver variability, and impractical to scale to the affected population of up to 1 billion affected individuals worldwide. Non-invasive imaging biomarkers have emerged as a key modality to address the major unmet need to diagnose, stage, and longitudinally monitor NAFLD. In this review, we critically examine the use of non-invasive imaging biomarkers to diagnose NAFLD, NASH, and fibrosis stage. Ultrasound and magnetic resonance imaging (MRI) biomarkers of liver fat can diagnose NAFLD. MRI proton density fat fraction (MRI-PDFF) is better than liver biopsy, particularly for following longitudinal changes in liver fat in clinical trials. Imaging biomarkers to reliably diagnose NASH are under investigation, but when used alone, continue to have only modest diagnostic accuracy. However, the fibrosis stage has the strongest association with liver decompensation and mortality, and elastography has emerged as a reliable biomarker for liver fibrosis. We review the combination of biomarkers to risk stratify patients and identify individuals needing treatment and the implications of longitudinal changes in liver stiffness measurement. •An improvement of ≥30% in liver fat on MRI-PDFF is associated with histologic improvement.•Combining MRE ≥3.3 kPa and FIB-4 ≥ 1.6 (MEFIB Index) predicts high-risk NAFLD.•Elevated liver stiffness measurements predict future hepatic decompensation.•MRE ≥ 4.67 kPa and ≥8 kPa predict cirrhosis and hepatic decompensation, respectively.